2021
DOI: 10.1002/anie.202100123
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electronic Structure and Size of Ultrastable Metalated Metal–Organic Frameworks with Enhanced Electroconductivity for High‐Performance Supercapacitors

Abstract: Utilization of metal-organic frameworks (MOFs) as electrodes for energy storage/conversion is challenging because of the low chemical stability and poor electrical conductivity of MOFs in electrolytes.Ananoscale MOF, Co 0.24 Ni 0.76 -bpa-200, possessing ultrahigh stability with uncommon semiconductor behavior (s = 4.2 10 À3 Sm À1 )w as fabricated. The MOF comprises ar obust hydrophobic paddlewheel and an optimized Co/Ni ratio,with consequent control over MOF size and the degree of conjugation of the coligand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…The specific capacitance of the working electrode (C s , F g À 1 ) in the three-electrode system in a 1 m H 2 SO 4 solution was evaluated from the discharge curve in GCD using Equation (5). 36] C S ¼ I Dt=ðm DVÞ (5) The specific capacity of the working electrode (Q s , mAh g À 1 ) in the three-electrode system in a KIÀ H 2 SO 4 electrolyte was evaluated from the discharge curve in GCD using Equation (6).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific capacitance of the working electrode (C s , F g À 1 ) in the three-electrode system in a 1 m H 2 SO 4 solution was evaluated from the discharge curve in GCD using Equation (5). 36] C S ¼ I Dt=ðm DVÞ (5) The specific capacity of the working electrode (Q s , mAh g À 1 ) in the three-electrode system in a KIÀ H 2 SO 4 electrolyte was evaluated from the discharge curve in GCD using Equation (6).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…A tremendous amount of research on how to increase their energy density have thus been conducted. [6][7] The introduction of redox capacity is an effective strategy to increase the specific capacitance of supercapacitors. [8] Doping redox active materials in carbon materials allows the composite materials to undergo a reversible Faradaic electrochemical reaction, resulting in additional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of hydrophobic paddle‐wheel SBUs can effectively avoid the attack of water molecules and hydroxide ions and therefore could be beneficial to electron transport [55] . In this regard, the multi‐carboxylate‐containing ligands were also documented to construct the hydrophobic and the paddle‐wheel‐like SBUs [56] . In 2021, Xia et al [56] .…”
Section: Non‐interpenetrating Pillar‐layered Mofs For Scsmentioning
confidence: 99%
“…In this regard, the multi‐carboxylate‐containing ligands were also documented to construct the hydrophobic and the paddle‐wheel‐like SBUs [56] . In 2021, Xia et al [56] . chose the hydrophobic H 2 camph (DL‐(±)‐camphoric acid) to connect distinct Co‐bpy or Co‐bpe motifs together to form 3D non‐interpenetrating pillar‐layered frameworks (bpa=1,2‐di(pyridin‐4‐yl)ethyne; bpy=4,4’‐bipyridine).…”
Section: Non‐interpenetrating Pillar‐layered Mofs For Scsmentioning
confidence: 99%
“…Notably, according to this strategy of documenting π ‐conjugated molecules, Xia et al adopted conjugated pillar ligands to co‐construct the conductive pillar‐layered MOFs systems, the achieved M‐MOFs (M = Co and Ni) could also display good capacitance retention of 86.5% after continuous 10 000 cycles and a maximum gravimetric capacitance of 1927.14 F g −1 (Figure 5d). [ 160 ] Apart from the good performances, this work provides a new strategy to construct highly conductive pillar‐layered MOFs reservoirs for the future because Bi and co‐workers found that the 3D conductive MOF‐based family could be expected to have advantages over the 2D MOF layers with quasi‐1D pores due to the dense stacks of 2D motifs. [ 161 ] Therefore, combining the strategy of designing 2D conductive MOFs with constructing pillar‐layered MOFs could be an optimal choice for future researchers.…”
Section: Co‐ or Ni‐based Mofs As Scs Electrodesmentioning
confidence: 99%